Empirical essays in international macroeconomics - Bénétrix, Agustín S. (Trinity College (Dublin, Ireland). Department of Economics, 2009)
This thesis is composed of three essays. The first one examines cases in which there is a large shift in a country's net foreign asset position due to the re-valuation of its foreign assets and / or foreign liabilities. The second essay studies the dynamic effect of positive shocks in different types of government spending on the real exchange rate of the European Monetary Union (EMU) countries. The last essay studies the dynamic response of real wages to positive shocks in five different types of government spending using annual data in a panel formed by EMU countries.

Revised versions of Chapters 2, 3 and 4 are published as journal articles: Chapter 2: The Anatomy of Large Valuation Episodes, Review of World Economics, 145(3): 489-511, October 2009. http://link.springer.com/article/10.1007%2Fs10290-009-0026-1

Chapter 3: Fiscal Shocks and the Real Exchange Rate, (with Philip Lane), International Journal of Central Banking, 9(3):1-32, September 2013. http://www.ijcb.org/journal/ijcb13q3a1.htm

Chapter 4: Fiscal Shocks and Real Wages, International Journal of Finance & Economics, 17(3): 203-220, July 2012. http://onlinelibrary.wiley.com/doi/10.1002/ijfe.452/pdf
Keywords: Economics, Ph.D.; Ph.D. Trinity College Dublin